THE FORMATION OF FUNCTIONAL INDICATORS IN THE MANAGEMENT OF THE TRAINING PROCESS OF LONG-DISTANCE RUNNERS AT THE STAGE OF ADVANCED SPECIALIZATION - Sultanov Usman Ibragimovich (Galaxy International Interdisciplinary Research Journal, 2023)
No matter what actions the athlete performs, the size, intensity and quality of these actions (coordination, technique and tactics) are determined by the functional reserve and bioenergetic capabilities of the body. In long-distance running, regular training loads, depending on their specific characteristics, gradually lead to the adaptation of the athletes' body. Since speed-strength endurance is one of the priority qualities in long-distance running, the possibility of achieving high sports results directly depends on the "central" nervous system, respiratory system, cardiovascular structure contraction speed and leg muscle components, which ensure their endurance quality. "Central" and "peripheral" components of quick-power endurance are functionally formed in a specific direction in long jump, middle and long-distance running of athletics (Pavlova O.I., Olimov M.S., Khalmuhamedov R.D.).